Implementasi Simba Dikantor Baznaz Kota Padang - Winda Oktarina; Syamsir Syamsir; Siti Wahyuni; Addibul Lutfi; Puput Sari Bulan; Adit Irawan; Randa Brasco (Universitas Palangka Raya, 2022)
The purpose of this study is to find out the form of SIMBA implementation at the Padang City BAZNAZ Office, to find out the obstacles to SIMBA implementation at the Padang City BAZNAZ Office and to find out the efforts or solutions in overcoming obstacles in SIMBA implementation at the Padang City BAZNAZ Office. This research uses a qualitative method, namely a method that focuses on reasoning based on objective social reality. The type of research used is a qualitative research method using a descriptive approach. The application of this qualitative method aims to make it easier to understand multiple realities, presenting an essential relationship between writing and reality in the field. This method is more sensitive and adjusts to the form of the value encountered. In using this method it aims to find problems more openly, so the writer will interview Baznas informants in the city of Padang, in which case the writer interviewed the Head of HR and General Affairs: Industriyadi, S.Sos.I, MA, and Staff: Bobi Iskandar. Data collection techniques using interviews, observation and documentation. Data analysis techniques in this study are data reduction, data presentation, and conclusions/verification. This application To facilitate the management of zakat is not solely carried out individually from muzakki to mustahiq, but is carried out by an institution that specifically handles zakat, namely amil zakat. In addition, the government has also issued Law no. 23 of 2011 concerning Zakat Management, which explains that the National Zakat Amil Agency is an institution that manages zakat nationally